2012
DOI: 10.1007/s10067-012-2132-z
|View full text |Cite
|
Sign up to set email alerts
|

Depression in obese patients with primary fibromyalgia: the mediating role of poor sleep and eating disorder features

Abstract: Depression is a prominent feature in fibromyalgia syndrome. Patients with fibromyalgia syndrome who are obese, with poor sleep quality, and those who have recurrent episodes of binge eating are at greater risk to develop depression. The aim of this cross-sectional study was to examine the hypothesis that the relationship between obesity and depression in patients with primary fibromyalgia syndrome is mediated by poor sleep, binge eating disorder (BED), and weight and shape concern. This study included 131 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…17 Several studies of obesity in FM patients, have also found significant associations between depression and BMI. 11,31,43 We confirm these results in our cohort; obese FM patients reported significantly higher PHQ-9 depression scores compared with normal-weight FM patients (13.2 [6.6] vs 10.5 [6], respectively). Like our study, they did not show an increased prevalence of anxiety.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…17 Several studies of obesity in FM patients, have also found significant associations between depression and BMI. 11,31,43 We confirm these results in our cohort; obese FM patients reported significantly higher PHQ-9 depression scores compared with normal-weight FM patients (13.2 [6.6] vs 10.5 [6], respectively). Like our study, they did not show an increased prevalence of anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…[8][9][10][11][12][13]43,47 This was surprising because we found a significant correlation between BMI and disability measured by HAQ-DI (r = 0.254; P < 0.0001) in agreement with previous reports, 32 and with data from the general population. 48,49 We did, however, find a strong correlation between HAQ-DI and FIQ physical impairment (r = 0.598, P < 0.001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In another study, 44.7% of FMS patients were obese and 36.8% were overweight. 37 These issues need to be investigated in JFMS.…”
Section: Discussionmentioning
confidence: 99%
“…In the general adult population, the prevalence of CWP has been reported to be around 10% [15,16], and for FM the number ranges between 1-4% depending on which ACR criteria used [16][17][18]. Except for presence of widespread pain with allodynia or hyperalgesia, individuals diagnosed with CWP/FM often experience symptoms such as fatigue, sleep disturbance, depression and/or anxiety and stiffness of muscles and joints [19][20][21]. Beyond these symptoms other factors could play a role in this pain condition such as female sex, obesity and increasing age [22,23].…”
Section: Symptoms Of Cwp/fmmentioning
confidence: 99%